Agustín Víctor Casasola: Images and gender in the contextof the mexican revolution (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2019)
Since the nineteenth century, the photographic record has been an invaluable source of historic information. Photographs, as social documents, may not only show the materiality of an epoch, they might also display, from disciplinary and methodological perspectives, the ideas of the world shared by a social group. From sociocultural studies and heeding the proposal of the calling roundtable, we propose to retrieve a photo series captured by the Casasola and sheltered by the archive named after them. The photographs were taken during the last years of the Porfiriato and up to the beginning of the nineteen twenties; most of them in the context of the Mexican Revolution. The selected images give us the opportunity to meditate about the discourses that can be read from gender perspective, showing how in the different places and practices in which social daily life goes by, we reproduce symbolically a series of ideas and practices that contribute to maintain the patriarchal discourse and fortify the limits imposed by gender.
Keywords: discourse; photographic images; Mexican Revolution; women; gender